Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Giải phương trình : \(\frac{\sin^{10}x+\cos^{10}x}{4}=\frac{\sin^6x+\cos^6x}{4\cos^22x+\sin^22x}\) ?
\(\Leftrightarrow\left(sin^4x+cos^4x\right)^2-2sin^4x.cos^4x=\frac{17}{32}\)
\(\Leftrightarrow\left[1-2sin^2x.cos^2x\right]^2-2sin^4x.cos^4x=\frac{17}{32}\)
Đặt \(sin^2x.cos^2x=\frac{1}{4}sin^22x=t\Rightarrow0\le t\le\frac{1}{4}\)
\(\Rightarrow\left(1-2t\right)^2-2t^2=\frac{17}{32}\)
\(\Leftrightarrow2t^2-4t+\frac{15}{32}=0\)
\(\Rightarrow\left[{}\begin{matrix}t=\frac{15}{8}\left(l\right)\\t=\frac{1}{8}\end{matrix}\right.\) \(\Rightarrow\frac{1}{4}sin^22x=\frac{1}{8}\Leftrightarrow2sin^22x=1\)
\(\Leftrightarrow cos4x=0\)
1.
\(\Leftrightarrow sin^2x\left(sinx+1\right)-2\left(1-cosx\right)=0\)
\(\Leftrightarrow\left(1-cos^2x\right)\left(sinx+1\right)-2\left(1-cosx\right)=0\)
\(\Leftrightarrow\left(1-cosx\right)\left(1+cosx\right)\left(sinx+1\right)-2\left(1-cosx\right)=0\)
\(\Leftrightarrow\left(1-cosx\right)\left(sinx+cosx+sinx.cosx-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cosx=1\Leftrightarrow...\\sinx+cosx+sinx.cosx-1=0\left(1\right)\end{matrix}\right.\)
Xét (1):
Đặt \(sinx+cosx=t\Rightarrow\left[{}\begin{matrix}\left|t\right|\le\sqrt{2}\\sinx.cosx=\frac{t^2-1}{2}\end{matrix}\right.\)
\(\Leftrightarrow t+\frac{t^2-1}{2}-1=0\)
\(\Leftrightarrow t^2+2t-3=0\Rightarrow\left[{}\begin{matrix}t=1\\t=-3\left(l\right)\end{matrix}\right.\)
\(\Leftrightarrow sin\left(x+\frac{\pi}{4}\right)=\frac{\sqrt{2}}{2}\)
\(\Leftrightarrow...\)
2.
\(\Leftrightarrow\sqrt{3}sinx.cosx+\sqrt{2}cos^2x+\sqrt{6}cosx=0\)
\(\Leftrightarrow cosx\left(\sqrt{3}sinx+\sqrt{2}cosx+\sqrt{6}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cosx=0\Leftrightarrow...\\\sqrt{3}sinx+\sqrt{2}cosx=-\sqrt{6}\left(1\right)\end{matrix}\right.\)
Xét (1):
Do \(\sqrt{3}^2+\sqrt{2}^2< \left(-\sqrt{6}\right)^2\) nên (1) vô nghiệm
e/
\(\Leftrightarrow1+cos2x+1+cos4x+1+cos6x=3+3cosx.cos4x\)
\(\Leftrightarrow cos2x+cos6x+cos4x-3cosx.cos4x=0\)
\(\Leftrightarrow2cos4x.cos2x+cos4x-3cosx.cos4x=0\)
\(\Leftrightarrow cos4x\left(2cos2x+1-3cosx\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos4x=0\Rightarrow x=\frac{\pi}{8}+\frac{k\pi}{4}\\2cos2x-3cosx+1=0\left(1\right)\end{matrix}\right.\)
\(\left(1\right)\Leftrightarrow2\left(2cos^2x-1\right)-3cosx+1=0\)
\(\Leftrightarrow4cos^2x-3cosx-1=0\)
\(\Rightarrow\left[{}\begin{matrix}cosx=1\\cosx=-\frac{1}{4}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=k2\pi\\x=\pm arccos\left(-\frac{1}{4}\right)+k2\pi\end{matrix}\right.\)
d/
\(\Leftrightarrow5\left(1+cosx\right)=2+\left(sin^2x-cos^2x\right)\left(sin^2x+cos^2x\right)\)
\(\Leftrightarrow5\left(1+cosx\right)=2+sin^2x-cos^2x\)
\(\Leftrightarrow5+5cosx=2+1-cos^2x-cos^2x\)
\(\Leftrightarrow2cos^2x+5cosx+2=0\)
\(\Rightarrow\left[{}\begin{matrix}cosx=-\frac{1}{2}\\cosx=-2\left(l\right)\end{matrix}\right.\)
\(\Rightarrow x=\pm\frac{2\pi}{3}+k2\pi\)
e/
\(\Leftrightarrow3\left(1-cos6x\right)-\left(2cos^26x-1\right)=4\)
\(\Leftrightarrow-2cos^26x-3cos6x=0\)
\(\Leftrightarrow cos6x\left(2cos6x+3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}cos6x=0\\cos6x=-\frac{3}{2}\left(l\right)\end{matrix}\right.\)
\(\Rightarrow6x=\frac{\pi}{2}+k2\pi\)
\(\Rightarrow x=\frac{\pi}{12}+\frac{k\pi}{3}\)
d/
\(\Leftrightarrow3\left(1-cos2x\right)-2\left(1-cos^22x\right)=5\)
\(\Leftrightarrow2cos^22x-3cos2x-4=0\)
\(\Leftrightarrow\left[{}\begin{matrix}cos2x=\frac{3+\sqrt{41}}{4}\left(l\right)\\cos2x=\frac{3-\sqrt{41}}{4}\end{matrix}\right.\)
\(\Rightarrow x=\pm\frac{1}{2}arccos\left(\frac{3-\sqrt{41}}{4}\right)+k\pi\)
Nghiệm xấu quá :(